Physical Culture, Bodily Practices and Dance in Late Nineteenth-century and Early Twentieth-century America (Review Article) - Thomas, Helen (Edinburgh: Edinburgh University Press, 2004)
RESUMEN: Several years ago I wrote a review article (Thomas, 1998) in three books published in 1995, which focused on the relations between the body, politics and performance, viewed through the lens of theatrical dance practices. In this review, I consider two books, published in the same year, 1999, which are also concerned with bodies, but not necessarily "special" (theatrical) dancing bodies: The Cultivation of Body and Mind in Nineteenth-Century American Delsartism (Nancy Lee Chalfa Ruyter, Greenwood Press: Wesporte Conn.,London, 1999); Dancing Class: Gender, Ethnicity, and Social Divides in American Dance, 1890-1920 (Linda J. Tomko, Indiana University Press: Blomington and Indianapolis, 1999). It is useful to consider these two studies together. Both studies turn the focus of attention away from dance as "art", in favour of other less well-documented aspects of physical culture, to consider their impact on everyday bodies, and on women's lives in particular. Both studies point to the importance of women's physical and cultural practices in the development of modern dance in America. Furthermore, as well as situating their work within the study of dance history, the authors seek to engage with feminist or women's studies, and cultural history.